Rukun Kifayah Islam (RKI) Masjid Agung Ibnu Batutah Kompleks Puja Mandala sebagai Ikatan Sosial Keagamaan Masyarakat Multikultural - Ramadhan, Jabaru; Aliffiati, .; Wiasti, Ni Made (Sunari Penjor : Journal of Anthropology, 2022)
The people around the Puja Mandala complex are religious people who respect each other, the congregation of the Great Ibn Battuta mosque also plays an important role as a forming medium that can reflect the general public the importance of the value of harmony in pluralistic life. As a commitment to maintaining harmony and an attitude of religious tolerance, the efforts made by the Great Mosque of Ibn Battuta include maintaining personal and institutional relationships with other religious parties. This is very important because religious leaders become role models in attitude. This study uses descriptive qualitative research methods using Functionalism Theory, Multiculturalism Theory, and Organizational Theory. The results of this study reveal that the plural society in the Puja Mandala complex has good communication relations, especially between Muslims and non-Muslims who maintain harmony with each other as a form of religious harmony.